2007
DOI: 10.1038/sj.onc.1210542
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β precursor-like protein APLP1 is a novel p53 transcriptional target gene that augments neuroblastoma cell death upon genotoxic stress

Abstract: The tumor suppressor p53 is a key modulator of the cellular stress response, inducing cell-cycle arrest, apoptosis, senescence and cell differentiation. To evaluate further the molecular mechanism underlying p53 function, the transcriptional profiles of proliferating and senescent WI-38 cells, both wild-type p53 expressers and counterparts with an inactivated p53, were compared by DNA microarray analysis. In particular, the amyloid-b precursor-like protein 1 (APLP1) is induced in senescent cells in a p53-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…CFD , known to be important in immune defense in tissue [48], possibly participates in inflammation of gastric epithelium [49]. APLP1 , a transcriptional target of p53, may be involved in cell death [50] and therefore vorinostat-induced expression of APLP1 may contribute to apoptotic cell death observed in our study. NQO1 inactivation has been associated with increased susceptibility to a variety of carcinogens [51], and has been related to the risk of colorectal cancer [52], [53].…”
Section: Discussionmentioning
confidence: 50%
“…CFD , known to be important in immune defense in tissue [48], possibly participates in inflammation of gastric epithelium [49]. APLP1 , a transcriptional target of p53, may be involved in cell death [50] and therefore vorinostat-induced expression of APLP1 may contribute to apoptotic cell death observed in our study. NQO1 inactivation has been associated with increased susceptibility to a variety of carcinogens [51], and has been related to the risk of colorectal cancer [52], [53].…”
Section: Discussionmentioning
confidence: 50%
“…In another study, the apoptosis triggering mechanism of AICD was shown to involve enhancement of p53-mediated apoptosis [103]. Recently, a study by Tang et al demonstrated that the APLP1 gene is a direct transcriptional target of p53 [104]. It was further shown that knock-down of APLP1 reduced stress-induced apoptosis in neuroblastoma cells, whereas overexpression of APLP1 enhanced it.…”
Section: Neuronal Survival and Apoptosismentioning
confidence: 95%
“…S3a). Also examined by qRT-PCR were PAI-1 (plasminogen activator inhibitor-1)22, IGFBP7 (insulin-like growth factor binding protein 7)23, MMP3 (matrix metallo-protease 3)24, BUB1 (budding uninhibited by benzimidazoles 1 homolog)25 and CDC20 (cell division cycle 20 homolog)26, which were reported to be upregulated (the former three) or downregulated (the latter two) at cellular senescence27 and predicted (IGFBP7: www2.ba.itb.cnr.it/p53FamTaG) or experimentally shown (the other four) to be transcriptionally regulated by p5322, 2527. These genes were found to be changed in expression in the expected directions (Fig.…”
mentioning
confidence: 99%